Records of Bornean felids in and around Tabin Wildlife Reserve, Sabah, Malaysia - Henry Bernard; Esther Lonnie Baking; Hisashi Matsubayashi; Abdul Hamid Ahmad (Cat Specialist Group, 2012)
We photo-captured four of the five species of Bornean wild cats in Tabin Wildlife Reserve (Tabin WR) and in the nearby forest fragments located within a matrix habitat of mature oil palm plantation. The four species were Sunda clouded leopard Neofelis diardi, Bornean bay cat Pardofelis badia, marbled cat Pardofelis marmorata, and leopard cat Prionailurus bengalensis. A fifth species, the flat headed cat Prionailurus planiceps, was photographed earlier in 2002 (Yasuda et al 2007), but was not detected during our study. The leopard cat was photographed from all sampling sites, but all other species were photographed only from the forest habitats of Tabin WR. Despite consisting mainly of regenerating secondary forest, Tabin WR may still constitute an important component for the preservation of the Bornean Wild cat species in Sabah